PEMULIHAN KERUGIAN KORBAN KEJAHATAN TERHADAP HARTA BENDA DALAM PERSPEKTIF HUKUM PIDANA - Mutiara Sri Melinda; Erdianto Erdianto; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Crimes against property in Indonesia have not been regulated perfectly in law so thatthey are still partial and require further implementing regulations for the sake of justice andwelfare of those concerned. One of the rights of the victim is to get compensation from theperpetrator so that it can help the victim to reduce his suffering. If the crime that befalls thevictim is a property crime with material losses, then the intended compensation is the returnof the victim's belongings or the perpetrator compensates for a number of victims' losses.positive in Indonesia and its implementation. And secondly, to find out the ideal punishmentfor criminal property crimes in Indonesia in the future.From the results of this research on legal issues, it can be concluded that there areseveral things that need to be done for the benefit and justice of law in Indonesia, both fromthe perspective of perpetrators and victims. Namely, first, regulation of criminal sanctionsagainst property in positive law in Indonesia and its implementation. In the event that thereare several arrangements, namely Article 98 of the Criminal Procedure Code, Law Number13 of 2006 concerning the Protection of Witnesses and Victims, Government RegulationNumber 35 of 2020 Amendments to Government Regulation Number 7 of 2018 concerningProvision of Compensation, Restitution and Assistance to Witnesses and Victims . In Islamiclaw, it is also known as the concept of Diyat. Besides that, there is also customary law thatoccurs because of habits that have existed from the past and are used as rules in society.Second, ideally the imposition of crimes against property in Indonesia in the future. In thiscase the researcher provides a new alternative in solving the problem of crimes againstproperty, namely where to propose compensation to be one of the main crimes that should beregulated in the types of Indonesian crimes. Seeing the many victims whose property will beharmed in the future. Suggestions from the author is that in the future criminal law reformsshould be carried out where there are rules that clearly regulate the compensation sufferedby victims of crimes against property.Keywords: Property, Victims, Compensation